A comparison of vertical reaction forces during propulsion of three different one-arm drive wheelchairs by hemiplegic users. (25th March 2013) - Mandy, Anne; Redhead, Lucy; McCudden, Carol; Michaelis, Jon
Abstract: Purpose : The aim of this pilot study was to compare the vertical reaction forces ( N ) generated in three different Action 3 manual one-arm drive wheelchairs: dual handrim, a lever drive and a Neater Uni-wheelchair (NUW). A CONFORmat® Pressure measurement mat, placed on top of the users' prescribed cushion, measured vertical force at the buttock/seat interface on both hemiplegic and non-hemiplegic sides in each wheelchair. Methods : Fifteen hemiplegic users were randomly assigned each wheelchair to drive around an indoor obstacle course. During propulsion of a multiple sensor, continuous measurement of force was recorded. Time taken to complete the circuit was recorded. Mean force and confidence intervals for each buttock were calculated per user per wheelchair. Results : The dual handrim produced the highest vertical force during propulsion under the right buttock (\def\newpage{\vfill \break } \nopagenumbers $ \bar x $ \newpage \end  = 484.43; SD = 55.4; p  < 0.001) and the lever drive produced the least force (\def\newpage{\vfill \break } \nopagenumbers $ \bar x $ \newpage \end  = 368.05; SD = 53.55; p  < 0.01). The NUW completed the course quickest ( p  < 0.01). Conclusions : The dual-handrim wheelchair requires the greatest vertical force during propulsion. Since increases in this seat vertical reaction force may be related to the propulsive force. Further investigation is indicated as this may be a significant factor for clinicians when prescribing one-arm drive wheelchairs. Implications for Rehabilitation: Review of clinical reasoning in prescribing wheelchairs. Addition of the Neater Uni-wheelchair to wheelchair services prescribing lists.